Benign Esophageal Stricture: Recent Advances in Endoscopic Dilation and Adjunctive Therapy - Gunawan Wijaya Setiawan (Universitas Methodist Indonesia, 2025)
Benign esophageal stricture is a clinically heterogeneous fibrostenotic condition that impedes swallowing, eating, medication intake, and overall health maintenance. Endoscopic dilation is still the best way to treat strictures, but many patients have them come back or don't respond to treatment, so they need to have the procedure done again and try different methods. This narrative literature review examines published evidence from the past decade regarding endoscopic dilation and alternative treatments for benign esophageal strictures. Evidence suggests that an etiology-based approach is optimal. For instance, peptic and inflammatory strictures necessitate vigorous intervention of the underlying inflammatory catalyst. Short anastomotic rings and focal mesh are good options for incisional therapy. Complex caustic, radiation-induced, and post-endoscopic resection strictures frequently require serial dilations in conjunction with alternative treatments. Recent advancements have improved patient selection instead of replacing dilation. There are still not many good comparative trials. Subsequent research ought to establish standardized definitions, document patient-reported outcomes, and develop risk-stratification algorithms for early adjunctive therapy. Keywords: esophageal dilation, esophageal stricture, incisional therapy, esophageal stent, mitomycin C